The effect of time of day and menstrual cycle on physical performance and psychological responses in elite female Tunisian volleyball players - Seddik, M.; Bouzourraa, M. M.; Ceylan, H. I.; Hamaidi, J.; Ghouili, H.; Chtourou, H.; Guelmami, N.; Dergaa, I.; Muntean, R. I.; Souissi, N. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The influence of circadian rhythms and menstrual cycle phases on athletic performance and psychological responses is critical for optimizing training and competition strategies for female athletes. This study aimed to investigate the effects of time of day and menstrual cycle phases on the physical performance and psychological responses of elite female Tunisian volleyball players.